CUSTOMER PREFERENCES IN CHOOSING A SECURITIES COMPANY - Ragil Pardiyono; Jahny Sastradiharja (JURNAL STIE SEMARANG, 2023)
Investing is not something foreign to the people of Indonesia. In general, people choose traditional investments that have low risk, such as deposits in banks, buying land, gardens, buildings, and precious metals. People feel safer by investing like that because the price of these goods will increase even though the return (investment return) is small. This changed after the 2000s, various groups have started to look at investments that can generate large returns. One form of investment that generates high returns is investment in the capital market. There is a decrease in the number of securities companies from year to year which was inversely proportional to the increase in individual investor type SID shares. The decline in the number of securities companies was caused by several companies being unable to compete due to the small number of customers. One of the factors causing the decline in the number of securities companies is the ability of marketing strategies. This research will measure the factors that become the preferences of prospective customers of securities companies in the decision to become their customers. The model used as a reference is the marketing mix. Data processing uses factor analysis which results in the formation of 5 factors which contain marketing mix derivatives.